Adaptive tuned vibration absorber based on magnetorheological elastomer-shape memory alloy composite. (1st February 2018) - Kumbhar, Samir B.; Chavan, S.P.; Gawade, S.S.
Highlights: MRE-SMA composite is used as stiffness tuning element in vibration absorber (ATVA). Results demonstrate smooth tuning of ATVA by changing stiffness of MRE and SMA. Pitfalls of SMA as ATVA have been minimized by MRE-SMA combination. Natural frequency of absorber is achieved through tuning stiffness of composite. Abstract: Shape memory alloy (SMA) is an attractive smart material which could be used as stiffness tuning element in adaptive tuned vibration absorber (ATVA). The sharp modulus change in SMA material during phase transformation creates difficulties for smooth tuning to track forcing frequency to minimize vibrations of primary system. However, high hysteresis damping at low temperature martensitic phase degrades performance of vibration absorber. This paper deals with the study of dynamic response of system in which SMA and magnetorheological elastomer (MRE) are combined together to act as a smart spring- mass-damper system in a tuned vibration absorber. This composite is used as two way stiffness tuning element in ATVA for smooth and continuous tuning and to minimize the adverse effect at low temperature by increasing equivalent stiffness. The stiffnesses of SMA element and MRE are varied respectively by changing temperature and strength of external magnetic field. The two way stiffness tuning ability and adaptivity have been demonstrated analytically and experimentally. The experimental results show good agreement with analytical results. The proposed composite is able to shift the stiffness consequently the natural frequency of primary system as well as reduce the vibration level of primary system by substantial mount.